Relationship between social support, resilience, and gratitude on happiness among young adults in Selangor, Malaysia. - Yan, Teo Jia; Ma’rof, Aini Azeqa; Abdullah, Haslinda (Human Resources Management Academic Research Society (HRMARS), 2024)
This study examines the intricate relationship between social support, resilience, and gratitude, and how these collectively impact happiness. Utilising current psychological theories, the study seeks to clarify how these positive psychology concepts impact the well being of young adults in Malaysia. A cross-sectional survey was conducted, comprising a total of 320 participants. Data on each variable was collected using validated scales. The investigation revealed robust positive connections between happiness and social support, resilience, and gratitude. In addition, a multiple regression study revealed that social support, resilience, and gratitude are important predictors of happiness, accounting for 51.4% of the variability in happiness scores. These results highlight the significance of improving social support, resilience, and gratitude through specific interventions to promote increased well being. The study also emphasizes the importance of tailoring mental health methods to align with cultural nuances, hence augmenting their efficacy in heterogeneous groups.